(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The research aims to determine the role of the dimensions of business intelligence represented by (data sources, data integration, data warehouse, data analysis, information presentation) in achieving sustainable performance represented by (economic performance, social performance, environmental performance), and the statistical program (SPSS) was adopted. . For the purpose of analyzing the data related to the field in question and showing the correlation and influence relationships between the variables, through several descriptive and analytical methods, by distributing (150) questionnaires to a sample of the administrative leaders in the Asiacell Telecom Company in Iraq, and in light of the statistical results, a set of conclusions, including: The contribution of business intelligence to achieving sustainable performance through the existence of moral relationships and influence between them. It came out with proposals, including: Giving more attention by the leaders of organizations to the dimensions that express business intelligence and working to adopt them for their role in sustainable performance.